The Diagnostic Yield of Colonoscopy Stratified by Indications. (27th July 2017) - Al-Najami, I.; Rancinger, C. P.; Larsen, Morten Kobaek; Spolén, E.; Baatrup, G.
Abstract : Introduction . Danish centers reserve longer time for screening colonoscopies and allocate the most experienced endoscopists to these cases. The objective of this study is to determine the diagnostic yield in colonoscopies for different indications to improve planning of colonoscopy activity and allocation of the highly skilled endoscopists. Methods . Nine hundred and ninety-nine randomly collected patients from a prospectively maintained database were grouped in defined referral indication groups. Five groups were compared in respect of the detection rate of adenomas and cancers. Results . Two hundred and eighty-nine of 1098 colonoscopies in 999 patients showed significant neoplastic findings, resulting in 591 adenoma resections. Eighty-five percent were treated with a snare resection, and 15% with endoscopic mucosa resection (EMR). Positive findings in the indication groups were (1) symptoms, 25%; (2) positive screening, 17%; (3) previous resection of adenomas, 45%; (4) previous resection of colorectal cancer, 15%; and (5) surveillance of patients with high-risk family history of cancer, 35%. Conclusion . The majority of adenomas found during colonoscopy can be treated with simple techniques. If individualized time slots are considered, the adenoma follow-up colonoscopies are likely to be the most time-consuming group with more than twice the number of adenomas detected as compared to other indications.